2023
DOI: 10.3390/cells12071081
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Biomarker Potential of Exosomal Non-Coding RNAs in Colorectal Cancer: An In Silico Characterization of Related Exosomal lncRNA/circRNA–miRNA–Target Axis

Abstract: Colorectal cancer (CRC) is one of the most common cancer types, ranking third after lung and breast cancers. As such, it demands special attention for better characterization, which may eventually result in the development of early detection strategies and preventive measures. Currently, components of bodily fluids, which may reflect various disease states, are being increasingly researched for their biomarker potential. One of these components is the circulating extracellular vesicles, namely, exosomes, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…This is consistent with the encouraging possibilities highlighted by Mezher et al, who emphasized the practicality of exosomal biomarkers in the field of oncological prognostics. 22 Similar to the methodology employed by 23. Dehghanbanadaki et al, 23 our meta-analytic approach F I G U R E 6 SROC curve of exosom-carried microRNAs for breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the encouraging possibilities highlighted by Mezher et al, who emphasized the practicality of exosomal biomarkers in the field of oncological prognostics. 22 Similar to the methodology employed by 23. Dehghanbanadaki et al, 23 our meta-analytic approach F I G U R E 6 SROC curve of exosom-carried microRNAs for breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the encouraging possibilities highlighted by Mezher et al, who emphasized the practicality of exosomal biomarkers in the field of oncological prognostics. 22 …”
Section: Discussionmentioning
confidence: 99%
“…They have a pivotal role in intracellular communication, cell signaling, tumor development and metastasis, as well as immune responses [ 128 ]. Exosomes produced by cancer cells are known to contain miRNA, and specific exosomal miRNAs offer potential as novel biomarkers for the early detection, prognosis, and treatment prediction of CRC [ 129 ]. Ogata-Kawata et al [ 130 ] identified a panel of serum exosomal miRNAs (let-7a, miR-1229, miR-1246, miR-150, miR-21, miR-223, and miR-23a) as promising biomarkers for CRC detection.…”
Section: Micrornasmentioning
confidence: 99%
“…The lncRNA SP100-AS1, identified as pivotal in CRC radioresistance and upregulated in radioresistant CRC tissues, interacts with ATG3 protein and sponges miR-622, affecting autophagic activity and possibly contributing to radioresistance. The SP100-AS1/miR-622/ATG3 axis might be targeted to enhance the efficacy of radiation therapy in CRC, signifying its importance in controlling radioresistant tumor cells [ 151 ]. Further investigations into additional RNA networks involved in radioresistance may provide more insights into regulating treatment responses in cancer.…”
Section: Unraveling the Complexity: The Interplay Of Lncrnas And Othe...mentioning
confidence: 99%